2022
DOI: 10.1002/cpz1.522
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Pattern Separation in Hippocampus by in Situ Hybridization

Abstract: Distinguishing different contexts is thought to involve a form of pattern separation that minimizes overlap between neural ensembles representing similar experiences. Theoretical models suggest that the dentate gyrus (DG) segregates cortical input patterns before relaying its discriminated output patterns to the CA3 hippocampal field. This suggests that the evaluation of neural ensembles in DG and CA3 could be an important means to investigate the process of pattern separation. In the past, measurement of ento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The fixed tissues were pretreated for protease digestion for 30 min at room temperature. The digested tissues were hybridized with appropriate H1a and Arc riboprobes according to instructions in manufacturer’s manual and previous studies and visualized to measure neural ensembles [ 21 , 28 ]. Nuclei were counterstained with 4′,6-diamidino-2-phenylindole (DAPI; Tocris bioscience, Bristol, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The fixed tissues were pretreated for protease digestion for 30 min at room temperature. The digested tissues were hybridized with appropriate H1a and Arc riboprobes according to instructions in manufacturer’s manual and previous studies and visualized to measure neural ensembles [ 21 , 28 ]. Nuclei were counterstained with 4′,6-diamidino-2-phenylindole (DAPI; Tocris bioscience, Bristol, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, studies have shown that circadian rhythms influence hippocampal plasticity and cortical development. The hippocampus is often associated with the formation of new associative memories, the storage of Table 1 The typical AS models memories independently, the retrieval of memories from partial cues, and the flexible application of stored memories to new situations [46]. With sleep deprivation, hippocampal plasticity decreases, hippocampal and cortical patterns are difficult to coordinate during NREM sleep, and theta oscillation regulation in the hippocampus has difficulty influencing learning and memory consolidation [47].…”
Section: The Mechanism Of Sleep Disorders In Asmentioning
confidence: 99%